Pelatihan Uji Pasar dengan Kuesioner sebagai Tindak Lanjut Pemasaran Green Laundry Perfume di SMK Bina Insan Mandiri - Rochmad, Imbuh; Novrisal, Dimas; Chandra, Agung (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
This training is designed to equip students with practical skills in conducting market testing before product launches. Training activities include preparing effective questionnaires, collecting data from potential customers, and analysing survey results to understand market preferences in depth. The training methods used include a combination of theoretical presentations, hands-on practice, and data analysis simulations, so that students gain real-world experience in conducting market research. The main objectives of this training are to improve students' proficiency in market research, mastery of research methodologies, application of real-world testing concepts in a business context, and development of entrepreneurial spirit and analytical skills. With this approach, the training is expected to not only provide theoretical understanding but also shape applied skills relevant to the needs of the business world, as well as promote the growth of innovative and data-driven young entrepreneurs.